IMIGLUCERASE TREATMENT IN GAUCHER'S DISEASE - Shah, Uzma; Nadeem, Naila; Husen, Yousef; Fadoo, Zehra (Journal of Ayub Medical College Abbottabad, 2007)
Gaucher's disease is an inherited lysosomal storage disorder with a deficiency of the enzyme glucocerbrosidase that manifests with clinical features of anemia, hepato-splenomegaly, skeletal destruction and organ dysfunction due to the accumulation of glucocerbrosides. There are several types of Gaucher's disease with varying prognosis and clinical progression of disease. We describe two cases followed at the Aga Khan University, Karachi, Pakistan, with different forms of the disorder. The enzyme Imiglucerase (Cerezyme, Genzyme) has been used to treat Type 1 Gaucher disease while the neuronopathic type has been resistant to therapy. We used Imiglucerase 60 µg/kg every 2 weeks in one patient with Type 1 Gaucher disease and followed hepatic, splenic volumes and blood counts. Treatment with Imiglucerase resulted in a decrease in splenic size, reduced requirements for transfusions and an improvement in cardiopulmonary symptoms. Keywords: Gaucher; Imiglucerase